Tinggalan Arca di Pura Puseh Desa Bale Agung Bukian, Payangan, Gianyar - Made Karmila Dewi, Ida Ayu; Palupi Titasari, Coleta (Humanis; Vol 22 No 2 (2018)DO - 10.24843/JH.2018.v22.i02.p04, 2018)
The statue is an archaeological remains which was built by people to fulfill certain needs in purpose. The archaeological remains in Bali are still in use and purified by its society by storing inside a temple, one of them is in Pura Puseh Desa Bale Agung Bukian, Payangan, Gianyar. This research has been done before by the Cultural Heritage Preservation Office, however it is just for conservation purpose and yet into deeper analysis. This research has an approach to acknowledge form, timeline, and function of an art statue remains in Pura Puseh Desa Bale Agung Bukian, Payangan, Gianyar. In this research, I used some theories such as form and functionality theory. I used some methods to solve these issues such as in first phase to collect data are observation, interview, and reviewing literature. The second phase are processing a data by analyzing data such as qualitative, iconographic, and comparative analysis. Based on the the analysis result, it can be concluded that the form of the statue remains in Pura Puseh Desa Bale Agung Bukian are 4 pieces of bhatara manifestation statues, 24 pieces of bhatari statues, and 10 pieces of fragments. The remains in Pura Puseh Desa Bale Agung Bukian can be put into Bali Madya style, because they had the same characteristic features with the Bali Madya’s statues group in Pucak Penulisan Temple, bhatari statue in Penataran Sasih Temple, bhatara statue in Sibi Agung Kesian Temple, and a couple of statues in Subak Taulan Kerobokan Temple. Until now, the remains in Pura Puseh Desa Bale Agung Bukian in Payangan, Gianyar are still being utilized by temple’s penyungsung as a place to worship. People and temple’s penyungsung considered that the remains had a magical religious power which the praying ceremony and piodalan was held in certain days. The remain which was stored in pelinggih believed by the people of Bukian village as a place to pray protection, safety, and fertility for agriculture and livestock of Bukian society.